INVESTIGATING TURNTAKING STRATEGIES IN CLASS DISCUSSIONS AMONG ESL ADULT LEARNERS - Noor Hanim Rahmat; Sharifah Amani Bte Syed Abdul Rahman; D Rohayu Mohd Yunos (University of Kuningan, 2015)
This quantitative study looked into class discussion strategies used by adult ESL learners. Findings revealed several benefits of class discussions for adult learners. Among some of them are, adult learners practice turn-taking skills in a non-combative environment. The sharing of ideas allowed freedom of thoughts among the learners. On the other hand, adult learners also learn to agree or disagree politely using turn-taking strategies. Finally, the benefits of class discussions may go beyond classroom needs such as improving critical thinking skills among learners. This ability is seen when learners participate in group work and discussions. Learners gain accessibility to participate comfortably in discussions when they are pun in a non-combative environment. This will thus give them the freedom to discuss any topics openly. This freedom will further enhance their general participation in the discussion. However, in a normal conversational process, speakers need to learn to speak up and also to give others space to voice their opinions. Learners need the knowledge of turn-taking skills in order to participate actively in the discussion. This turn-taking skills can be taught in ESL classrooms through class discussions.Â Keywords: ESL classroom, adult learners, class discussion strategies, general participation